MRI phase changes in multiple sclerosis vs neuromyelitis optica lesions at 7T - Sinnecker, Tim; Schumacher, Sophie; Mueller, Katharina; Pache, Florence; Dusek, Petr; Harms, Lutz; Ruprecht, Klemens; Nytrova, Petra; Chawla, Sanjeev; Niendorf, Thoralf; Kister, Ilya; Paul, Friedemann; et al. (Neurology® neuroimmunology & neuroinflammation, 2016)
OBJECTIVE: To characterize paramagnetic MRI phase signal abnormalities in neuromyelitis optica spectrum disorder (NMOSD) vs multiple sclerosis (MS) lesions in a cross-sectional study. METHODS: Ten patients with NMOSD and 10 patients with relapsing-remitting MS underwent 7-tesla brain MRI including supratentorial T2*-weighted imaging and supratentorial susceptibility weighted imaging. Next, we analyzed intra- and perilesional paramagnetic phase changes on susceptibility weighted imaging filtered magnetic resonance phase images. RESULTS: We frequently observed paramagnetic rim-like (75 of 232 lesions, 32%) or nodular (32 of 232 lesions, 14%) phase changes in MS lesions, but only rarely in NMOSD lesions (rim-like phase changes: 2 of 112 lesions, 2%, p < 0.001; nodular phase changes: 2 of 112 lesions, 2%, p < 0.001). CONCLUSIONS: Rim-like or nodular paramagnetic MRI phase changes are characteristic for MS lesions and not frequently detectable in NMOSD. Future prospective studies should ask whether these imaging findings can be used as a biomarker to distinguish between NMOSD- and MS-related brain lesions.